Pengaruh Luas Lahan, Jumlah Tenaga Kerja dan Modal terhadap Pendapatan Petani Sayur di Kampung Ariepi Distrik Kosiwo Kabupaten Kepulauan Yapen - John Frits Ayomi; Agustina Karowa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of land area, number of workers and capital on the income of vegetable farmers in Ariepi Village, Kosiwo District, Yapen Islands Regency. The population in this study were all vegetable farmers in Ariepi Village, Kosiwo District, Yapen Islands Regency. The research sample was Ariepi Village I and Ariepi Village II, Ariepi, Kosiwo District, Yapen Islands Regency. The data collection technique used in this study was observation through interviews with vegetable farmers and analyzed using multiple linear analysis with the help of SPSS 22.0 for windows. The results of this study found that (a) there was a significant simultaneous effect between land area, number of workers and capital on the income of vegetable farmers in Ariepi Village, Kosiwo District, Yapen Islands Regency; (b) there was a positive and significant partial effect between land area, number of workers and capital on the income of vegetable farmers in Ariepi Village, Kosiwo District, Yapen Islands Regency. This study shows the contribution of the variables of land area, number of workers and capital to income of 84.6%, the rest, namely 15.4% is influenced by other variables not included in this study.